1999
DOI: 10.2307/2656920
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of somaclonal variation in plants of black spruce (Picea mariana, Pinaceae) and white spruce (P. glauca, Pinaceae) derived from somatic embryogenesis and identification of some factors involved in genetic instability

Abstract: Plants of black spruce (Picea mariana, N = 7047 individuals) and white spruce (P. glauca, N = 3995 individuals) were regenerated from a total of 87 clones over a 5-yr period by somatic embryogenesis to study factors that might be associated with the appearance of variant phenotypes. Morphological evaluation of the plants showed several types of variation. These variations were grouped into nine types: dwarfism (type A), reduced height with various form anomalies (types B, C, and D), needle fasciation (type E),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
3
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 17 publications
2
58
3
2
Order By: Relevance
“…The stability reported here is not described in other species, in which polyploidisation was found during somatic embryogenesis (23)(24)(25)(26)(27). Endemann [27] found that tetraploidy occurs 8% of the clones tested over a culture period of 7 years in Quercusrobur.…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…The stability reported here is not described in other species, in which polyploidisation was found during somatic embryogenesis (23)(24)(25)(26)(27). Endemann [27] found that tetraploidy occurs 8% of the clones tested over a culture period of 7 years in Quercusrobur.…”
Section: Resultscontrasting
confidence: 68%
“…The samples were fixed in FAA (formaldehyde/acetic acid/ ethanol=10:5:85 v/v/v) for 48 h, followed by 30 min of dehydration at increasing ethanol gradations [25,50,75,95, 100% (v/v)]; dehydration was performed twice for each step. Ethanol was replaced by gradual dilution with trichloroethane solution.…”
Section: Histological Analysismentioning
confidence: 99%
“…In our study with P. pinaster, after 12 months of ex vitro conditions, 50% of the plants in which plagiotropism was initially detected and started to revert to orthotropism. Similarly, plagiotropic growth was also initially detected in plants of Larix (Ewald 1999) and in Picea (Tremblay et al 1999) propagated by SE, but after approximately 5 years a normal orthotropic growth was completely restored in these plants.…”
Section: Discussionmentioning
confidence: 61%
“…(ahloowalia y sherington , osuji et al 1997, Tremblay et al 1999, mehta y angra 2000); (b) patrones isoenzimáticos, que se basan en la presencia de isoformas de enzimas específicas, que tienen la misma actividad, pero con diferente estructura molecular (Jarret y Litz 1986, chen et al 1998, müller-starck 1998, seo et al 2004; (c) los basados en proteínas de reserva de las semillas (maddock et al 1985, campa et al 2004, martín-cuevas et al 2004); y (d) aquellos basados en el ADN, los cuales constituyen el tema específico de esta revisión (Picca et al 2004).…”
Section: Técnicas Utilizadas Para La Detección Y Cuantificación De Vaunclassified
“…Varios autores recomiendan que, al usar marcadores moleculares, deben combinarse al menos dos metodologías para una corroboración exacta y así evitar falsos positivos (ooms et al 1987, speeckaert y Jacobs 1988, Jiménez 1996, osuji et al 1997, chen et al 1998, Tremblay et al 1999, Feuser et al 2003, Kubis et al 2003.…”
Section: Definición Y Clasificación De Marcadores Moleculares Basadosunclassified